Best answers to the 201 most frequently asked interview questions [ - DeLuca, Matthew J.; DeLuca, Nanette F. (New York : McGraw-Hill, 2010)
From the Publisher: Answers that will get you hired-from the bestselling interview guide, now completely updated! In today's job market, there are thousands of qualified candidates battling it out for a few jobs. Beat out the competition and learn how to give the best interview with Best Answers to the 201 Most Frequently Asked Interview Questions-the essential job-seeking weapon you need to answer the thought-provoking or unexpected questions that potential employers use to weed out candidates. Career experts, Matthew and Nanette DeLuca, coach you through every possible question you'll encounter, along with the secret motivation behind them-including those you may not want to be asked but must answer. In this updated edition,you'll learn how to: Gracefully address a lost job; Tactfully discuss salary requirements; Take control of theinterview. With Best Answers to the 201 Most Frequently Asked Interview Questions, you'll never be at a loss for words on any interview
1. Talking is not communicating -- 2. Who are you? what hould you disclose? -- 3. Examining your choices : what are you getting yourself into? -- 4. "So glad to meet you" : the interview begins -- 5. Who are you? -- 6. Work smarts -- 7. What have you done? (and what can you do for us?) -- 8. How will you fit in? (or will you?) -- 9. How many ways can you spell stress? -- 10. Taking control of the interview -- 11. Don't go there! questions you may
not want to be asked-but may have to answer -- 12. Now it is your turn : questions to raise -- 13. Whew! now what?
Includes index
Previous ed.: 1997
Keywords: Employment interviewing